PENGARUH BUDAYA PERUSAHAAN DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PERTAMINA RU III PLAJU PADA AWAL TRANSFORMASI PERTAMINA - ERWIN WIDIARTA; BADIA PERIZADE; ZUNAIDAH . (Program Studi Magister Manajemen FE Unsri, 2015)
The purpose of this research is to find out the influence of Corporate Culture and Transformational Leadership partially or jointly to the performance of the Pertamina RU III employee after 5 years Transformation in Pertamina. This study used a descriptive survey method approach. Survey method is a research method in which information is collected through the use of questionnaires. The number of sample were 8 x total of research indicator (14 indicators). The numbers of total sample were 112 respondents, were about 16,5 % of 680 population of Pertamina RU III Plaju. Regarding to the title of this research, the beginning phase was 2008 to 2013, and the population in this study were the employee of Pertamina RU III who have worked at least 5 years. Essential things that must be considered in writing the questionnaire, the determination of the list of questions, as well as the format of the questionnaire design, as well as using infrencial analysis with multiple linear regression analysis model (multiple regression analysis). The results showed that Corporate Culture variable (X1) which partially have a significant influence to the employee performance (Y), and the same thing for Transformational Leadership variable (X2), partially has a significant effect to the employee performance (Y). This is indicated by the significance p-value is smaller than alpha value of 0.05. Furthermore, from the results of the F test (Simultaneous Test), Corporate Culture (X1) and Transformational Leadership (X2) have a significant influence to performance of Pertamina RU III Plaju employee (Y).